ROADBLOCKS TO PROFICIENCY: TOEFL READING COMPREHENSION CHALLENGES FOR UNIVERSITY STUDENTS - Agung Wicaksono; Sulistyani Sulistyani; Suhartono; Khoiriyah; Mahendra Puji Permana Aji (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This research examines the challenges university students encounter in the TOEFL reading comprehension section driven by low TOEFL proficiency among students. using a qualitative approach, the study identifies key difficulties learners face and the factors behind these struggles. data were gathered through questionnaires administered to 35 English language Education undergraduates at the University of Nusantara PGRI Kediri in East java, Indonesia. The questionnaire data were analyzed through cleaning, organizing, and interpreting responses to extract meaningful insights. The analysis of the responses revealed common obstacles, such as insufficient vocabulary, trouble with complex sentence structures, ineffective reading strategies, poor time management, and limited exposure to academic texts. Additionally, students cited anxiety and low confidence as psychological hurdles impacting their performance. The results indicate that both language proficiency and test-taking strategies significantly influence students' success in TOEFL reading comprehension. The study emphasizes the importance of modifying reading instruction to enhance academic reading skills and test preparation strategies, thereby better preparing students for standardized English proficiency exams.